DAMPAK PEMEKARAN DESA DALAM PEMBANGUNAN INFRASTUKTUR (Studi Kasus Pada Desa Penampaan Uken Kecamatan Blangkejeren Kabupaten Gayo Lues) - Harahap, Sella Ayu Wandira (PERSPEKTIF, 2015)
This study aims to analyze the impact of the expansion in the availability of facilities and infrastructure (infrastructure) in Desa Penampaan Uken Kecamatan Gayo Lues kabupaten Blangkejeren. The form ofthis research isdescriptive method with qualitative approach with a view to determine the impact of the expansion in infrastructure development in Desa Penampaan Uken. Based on the results of a study conducted by researchers at Desa penampaan Uken found that the information infrastructure build focuses on building roads, bridges, mosques while the administration for infrastructuree to service to the community such as the village head office is still there in the village and the impact over desa penampaan uken expansion occurs very significant visible from infrastructure development, where people feel very positive impact the ease of accessing the location and implement mobility.